Associations between the von Willebrand Factor—ADAMTS13 Axis, Complement Activation, and COVID-19 Severity and Mortality - Sinkovits, György; Réti, Marienn; Müller, Veronika; Iványi, Zsolt; Gál, János; Gopcsa, László; Reményi, Péter; Szathmáry, Beáta; Lakatos, Botond; Szlávik, János; Bobek, Ilona; Prohászka, Zita Z.; Förhécz, Zsolt; Mező, Blanka; Csuka, Dorottya; Hurler, Lisa; Kajdácsi, Erika; Cervenak, László; Kiszel, Petra; Masszi, Tamás; Vályi-Nagy, István; Prohászka, Zoltán (Thrombosis and Haemostasis, 2022)
Background Endothelial and complement activation were both associated with immunothrombosis, a key determinant of COVID-19 severity, but their interrelation has not yet been investigated.Objectives We aimed to determine von Willebrand factor (VWF) antigen (VWF:Ag) concentration, VWF collagen binding activity (VWF:CBA), a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13 (ADAMTS13) activity (ADAMTS13:Ac), and their ratios in hospitalized COVID-19 patients, and to investigate how these parameters and their constellation with complement activation relate to disease severity and in-hospital mortality in COVID-19.Methods Samples of 102 hospitalized patients with polymerase chain reaction-confirmed severe acute respiratory syndrome coronavirus 2 positivity were included in our observational cohort study. Patients were stratified according to the peak severity of COVID-19 disease in agreement with the World Health Organization ordinal scale. Twenty-six convalescent plasma donors with previous COVID-19 disease formed the control group. VWF:Ag concentration and VWF:CBA were determined by enzyme-linked immunosorbent assay (ELISA); ADAMTS13:Ac was determined by fluorescence resonance energy transfer. Complement C3 and C3a were measured by turbidimetry and ELISA, respectively. Clinical covariates and markers of inflammation were extracted from hospital records.Results VWF:Ag and VWF:CBA were elevated in all groups of hospitalized COVID-19 patients and increased in parallel with disease severity. ADAMTS13:Ac was decreased in patients with severe COVID-19, with the lowest values in nonsurvivors. High (> 300%) VWF:Ag concentrations or decreased (< 67%) ADAMTS13:Ac were associated with higher risk of severe COVID-19 disease or in-hospital mortality. The concomitant presence of decreased ADAMTS13:Ac and increased C3a/C3 ratio—indicating complement overactivation and consumption—was a strong independent predictor of in-hospital mortality.Conclusion Our results suggest that an interaction between the VWF-ADAMTS13 axis and complement overactivation and consumption plays an important role in the pathogenesis of COVID-19.
Keywords: ADAMTS13 protein; complement activation; COVID-19; survival analysis; von Willebrand factor